Knowledge and Perception of Diphtheria Vaccine Messages on Radio among Residents of Ungogo Local Government Area, Kano State - Abdullahi Abdullateef; Mainasara Yakubu Kurfi; Ololade Olatunji Lateef; Omolara Oluwabusayo Akin-Odukoya; Muhammad Ridwan (Budapest International Research and Critics University, 2025)
The re-emergence of diphtheria has become noticeable in Nigeria particularly in Kano state. This study assessed the knowledge level and perception of diphtheria vaccine messages on radio among residents of Ungogo Local Government Area, Kano State. To achieve this, the study employs survey method to quantify the knowledge and perception of the population of study.400 questionnaires are administered and nothing less than 390 are retrieved in both Rijyar Zaki and Tudun Fulani communities. The findings revealed that the residents had knowledge of diphtheria vaccine and radio remains the most important medium for disseminating diphtheria vaccine messages in Ungogo Local Government Area, Kano State. However, about 58.9 percent agreed that diphtheria vaccine is only necessary for children. 66.6 percent agreed that diphtheria vaccine message increased their confidence on the safety and efficacy of the vaccine. Frequency distribution tables are used to present and anlayse data generated from the field. The results of the study showed that the residents perceived diphtheria vaccine messages positively but 33.3 percent did not discuss about diphtheria with their friends, families and community members.